Integrasi Pendidikan Modern dan Klasik: Studi Pemikiran K.H. Ahmad Dahlan - Sayyid Muhammad Indallah (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2022)
This article aims to explain the thought of Ahmad Dahlan on the educational concept. Ahmad Dahlan is an enlightener who initiated the concept of Islamic-based modern education. This is qualitative research and library research with a historical approach. The data was analyzed using descriptive methods. The result showed that Ahmad Dahlan initiated an integrated-educational system from classical and modern education to solve the Muslims’ problems in facing knowledge and science during the colonialism period